Phrenic nerve palsy during cryoballoon ablation of atrial fibrillation: a minor complication or a wolf in sheep's clothing? Insights on late arrhythmia recurrences from a propensity score-matched analysis - Cecchini, Federico; Mugnai, Giacomo; Maj, Riccardo; Rubboli, Andrea; Del Monte, Alvise; Della Rocca, Domenico Giovanni; Almorad, Alexandre; Sieira, Juan; Marinelli, Alessio; Costa, Alessandro; Bonapace, Stefano; Molon, Giulio; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPulmonary vein isolation (PVI) has become the cornerstone of percutaneous atrial fibrillation (AF) treatment, and cryoballoon ablation (CB-A) has been shown to be non-inferior to radiofrequency (RF) ablation in terms of safety and efficacy. Hemi diaphragmatic paralysis, secondary to right phrenic nerve palsy (PNP), is the most common complication associated with cryoballoon ablation, occurring in 1.1%–6.2% of procedures. Although, in the literature, PNP appears to not jeopardize the acute electrical isolation of the right-sided pulmonary veins, its occurrence forces the electrophysiologist to immediately stop cryoenergy delivery, thus resulting in a shorter cryo-application time.AimsThe purpose of the analysis is to understand whether the occurrence of intraprocedural PNP can be related to an increased risk of developing atrial fibrillation/atrial flutter (AT/AF) recurrences during the follow-up.Methods and resultsWe retrospectively enrolled 116 consecutive patients who experienced PNP during PVI using the second-generation cryoballoon. This group was compared using 1:1 propensity score (PS) and caliper matching with a cohort of patients who did not present PNP. After the matching, 108 patients with CB-A related phrenic nerve palsy (PNP+ group) were analyzed and compared with 108 patients who did not experienced PNP (PNP- group). After a median follow-up of 19 [12.0, 31.0] months, the success rate was significantly lower in the PNP+ group compared to the control group (57.4% vs. 78.7%, Log-Rank p = 0.001). Patients with a history of PNP had an almost threefold higher risk of developing arrhythmia recurrences during follow-up compared to their counterparts (HR: 2.813, 95% CI: 1.470–5.385, p = 0.002). Patients who experienced PNP showed a trend toward a higher need for RF touch-up compared to the counterpart (p = 0.06). Left atrial diameter (Lad), need of cardioversion to restore sinus rhythm after PVI, together with PNP were found to be independent predictors of late arrhythmia relapses. No major complications occurred in the entire population.ConclusionsThe present study showed that PNP, although typically reversible and without long-term sequelae, is associated with a significantly lower success rate of CB-A PVI and a higher risk of arrhythmia recurrences.